Нестандартні форми зайнятості в умовах формування мережевої економіки - Кравчук, Оксана Іванівна (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2016)
Prerequisites of precarious labor relations during the formation of network economy were discussed. The essence of the characteristic features, advantages and disadvantages of using a virtual distance employment were defined at the individual, micro and macro levels.